Bevacizumab at first recurrence after standard radio-chemotherapy is associated with improved overall survival in glioblastoma patients with large tumor burden. Issue 2 (20th September 2018) - Nguyen, Huy Tram; Nguyen, Nhung; Liu, Liang Yen; Dovek, Laura; Lenchner, Daniel; Harris, Robert; Ozer, Byram; Ravelo, Arliene; Sommer, Nicolas; Sim, Myung Shin; Elashoff, Robert; Green, Richard; et al.
Abstract: Background: Since its approval for use in recurrent glioblastoma (GBM), the survival benefit of bevacizumab (Bev) remains to be demonstrated. To address this issue, we retrospectively examined survival from first recurrence in patients treated with Bev, lomustine (CCNU), or Bev/CCNU. Methods: We identified 168 primary GBM patients diagnosed at UCLA and Kaiser Permanente LA who received upfront radio-chemotherapy, followed by Bev and/or CCNU at first recurrence. Three patient groups, contemporaneously diagnosed from 2009 through 2015, were identified: (1) patients treated with Bev alone (n = 49), (2) CCNU alone (CCNU 09-15) (n = 36), and (3) Bev/CCNU (n = 53). Another CCNU control group (n = 30) diagnosed from 2001 through 2004 (CCNU 01-04) was also derived. We measured tumor size at first recurrence treatment initiation, using bidimensional (2D) and volumetric (3D) techniques, and analyzed overall survival (OS) from first recurrence. Results: Among the entire cohort, larger tumor size at first recurrence was associated with poorer survival. The CCNU 01-04 group had similar tumor size as the Bev arms and low Bev crossover (7%). Treatment with Bev was associated with improved survival in patients with large tumor 2D measurements: Median OS for Bev and Bev/CCNU groups were 6.71 mo (n = 27) and 6.97 mo (n = 36) vs 4.03 mo (n = 10) in CCNU 01-04. Analysis by 3D measurement yielded similar results. Interestingly, the CCNU 09-15 group showed the highest survival, likely due to smaller tumor size and crossover to Bev (69%). Conclusion: Survival advantage from Bev treatment was observed only among patients with large tumor burden as determined by either 2D or 3D measurement.